Empiricism and Rationalism in Islamic View: Empirisme dan Rasionalisme dalam Pandangan Islam - Kusuma, Kumara Adji (Universitas Muhammadiyah Sidoarjo, 2025)
The question of whether an object can inform a subject of its inherent nature reveals complexities in the subject-object relationship in perception. Human perception is inherently limited by the physiological structures of the senses, and thus, reality is interpreted rather than directly experienced. For instance, the color orange is not an inherent trait of an object but a perception shaped by the human eye's capacity to detect certain wavelengths of light. Variations in sensory structures across species highlight that other beings may perceive the same object differently; many animals, for instance, have distinct visual and auditory ranges, allowing them to see ultraviolet light or hear frequencies beyond human capacity. This limitation of human senses, however, is often overcome through technology—such as telescopes, microscopes, and specialized audio equipment—enabling insights beyond natural perception. Philosophically, this emphasizes the role of the intellect in compensating for sensory limitations, facilitating a structured understanding of phenomena that are otherwise inaccessible. Different epistemologies, including empiricism and rationalism, debate whether the senses alone or in conjunction with reason reveal truth, while Islamic perspectives emphasize a harmonious relationship between the two, with both seen as essential yet ultimately limited in understanding metaphysical or divine truths. This interplay between sensory perception and intellectual inference demonstrates the intricate processes humans employ to approximate an understanding of reality and its complexities. Highlights: Perception’s Limits: Senses offer partial, not full, reality. Tech’s Role: Extends perception beyond natural limits. Philosophy’s Insight: Highlights sensory and perceptual boundaries. Keywords: Subject-object-perception, sensory limitations, epistemology, intellect, human perception